Texture Improvement of Filamentous Fungi Burger Derived from Biomass of Rhizopus oligosporus: Impact of Binding Agent on Physical, Sensory, and Microstructure - Wimbasara, Dimas Fathullah; Wikandari, Rachma; Setiowati, Arima Diah; Sar, Taner; Taherzadeh, Mohammad J. (Trends in Sciences, 2025)
Despite its high nutritional value and low environmental impact, the nature of filamentous fungal hyphae might resemble the appearance of meat fibers. These properties make filamentous fungi as a promising protein alternative in the future. However, the texture of the mycelium is too weak to resemble meat fibers. This study was aimed to obtain non-animal binding agent to improve the texture of burger patty produced by fungal biomass of Rhizopus oligosporus. Different binding agents including sodium tripolyphosphate, transglutaminase, pectin, and modified tapioca were added to the fungi burger patty. The texture was analyzed by texture profile analyzer and sensory test. The texture profile analysis (TPA) showed that the addition of 10 % modified tapioca starch improved the patty structure, decreasing cooking loss by 46.05 %, while increasing hardness by 105.15 %, and chewiness by 83.55 %. Microstructure images confirm this finding by showing a compact and dense structure with discernible reduce in air pockets. This finding is in line to sensory evaluation result, in which the panels confirmed the improvement of fungi burger hardness. The Fourier Transform Infrared Spectroscopy (FTIR) result showed that the improvement might be due to the increase in hydrophobic interactions, hydrogen bonds, and disulfide bonds. These bonds were responsible for creating and stabilizing the structure of meat analogue. Overall, modified tapioca is a low-cost binding agent for texture improvement of fungi burger made from R. oligosporus biomass. HIGHLIGHTS Addition of binding agent improved the texture of mycoprotein burger. Addition of 10 % modified tapioca starch showed the best texture properties. Addition of modified tapioca starch increased the compactness of fungal mycelium. Hydrophobic interactions, hydrogen, and disulfide bonds contributed to texture. GRAPHICAL ABSTRACT